Changes in tone, setting, and publisher: Indigenous literatures of Australia and New Zealand from the 1980s to today - Henningsgaard, Per (2016)
This article examines four novels written since 1980 by two Aboriginal Australian authors and two Maori authors. Two of the four novels were written near the beginning of this period and feature settings that are contemporary with their publication; The Day of the Dog by Aboriginal Australian author Archie Weller was published in 1981, while Once Were Warriors by Maori author Alan Duff was published in 1990. The other two novels (That Deadman Dance by Aboriginal Australian author Kim Scott and The Trowenna Sea by Maori author Witi Ihimaera) are works of historical fiction written in the last decade. The shift in tone between the earlier novels and the more recent novels is particularly remarkable. Coupled with the shift in tone, the settings have changed. It is tempting to ascribe the shifts in tone and setting over this 30-year period to the changing social and political realities surrounding the issue of indigenous relations in the two nations. And these factors undoubtedly played an important role in the aforementioned shifts; indigenous authors writing today are responding to a different social and political reality compared to indigenous authors writing in the 1980s and early 1990s. What this explanation overlooks, however, are the concurrent changes in the publication of indigenous literature and how these might contribute to the types of changes noted above. Indigenous writers are now writing for an international literary marketplace. This article makes it clear that there are significant implications to the shift from indigenous literature being published by small to medium-sized local publishing houses, to indigenous literature being published by the local arm of a multinational conglomerate.